Disruption of a Regulatory Network Consisting of Neutrophils and Platelets Fosters Persisting Inflammation in Rheumatic Diseases - Maugeri, Norma; Rovere-Querini, Patrizia; Manfredi, Angelo A. (Frontiers in Immunology, 2016)
A network of cellular interactions that involve blood leukocytes and platelets maintains vessel homeostasis. It plays a critical role in the response to invading microbes by recruiting intravascular immunity and through the generation of Neutrophil Extracellular Traps (NETs) and immunothrombosis. Moreover it enables immune cells to respond to remote chemoattractants by crossing the endothelial barrier and reaching sites of infection. Once the network operating under physiological conditions is disrupted, the reciprocal activation of cells in the blood and the vessel walls determines the vascular remodelling via inflammatory signals delivered to stem/progenitor cells. A deregulated leukocyte/mural cell interaction is an early critical event in the natural history of systemic inflammation. Despite intense efforts, the signals that initiate and sustain the immune-mediated vessel injury, or those that enforce the often-prolonged phases of clinical quiescence in patients with vasculitis, have only been partially elucidated. Here we discuss recent evidence that implicates the prototypic Damage-Associated Molecular Pattern/ alarmin, the High Mobility Group Box 1 (HMGB1) protein in systemic vasculitis and in the vascular inflammation associated to systemic sclerosis. HMGB1 could represent a player in the pathogenesis of rheumatic diseases and an attractive target for molecular interventions.